FITOREMEDIASI AIR TERCEMAR TIMBAL (Pb) DENGAN Lemna minor DAN Ceratophyllum demersum SERTA PENGARUHNYA TERHADAP PERTUMBUHAN Lactuca sativa - Anjar Aris Munandar; Zaenal Kusuma; Sugeng Prijono; Rony Irawanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The pollution of water and soil caused by human causes environmental damage especially on agricultural land that resulted in the reduced growth and yield of plants. This research aimed to understand the ability of aquatic plants in accumulating lead (Pb) in water and its influence on lettuce growth. The treatments consisted of A1: Plant Lemna minor 2 ppm Pb, A2: Ceratophyllum demersum 5 ppm Pb, A3: Lemna minor 2 ppm Pb, A4: Ceratophyllum demersum 5 ppm Pb, A5: 2 ppm Pb without plants (control 1), and A6: 5 ppm Pb without plants (control 2). The results showed that the aquatic plants effectively decreased Pb concentration in water by 81.1% for Ceratophyllum demersum and by 75.5% for Lemna minor. The use of remediated water for watering lettuce resulted in affected growth and yield of lettuce.